Engaging the international community during the 2015 Middle East respiratory syndrome outbreak in the Republic of Korea - Minwon Lee; Hoohee Nam; Sun-Gyu Lee; Ok Park; Youngmee Jee; Kidong Park (World Health Organization Regional Office for the Western Pacific, 2016)
The 2015 Middle East respiratory syndrome (MERS) outbreak in the Republic of Korea, which started with an imported case and spread throughout the country with a total of 186 cases, revealed the vulnerabilities of the health-care system of the country. The situation was compounded by the unique health-care settings in the Republic of Korea, including crowded emergency departments and large numbers of hospital visitors seeking care at multiple hospitals. To assist with the outbreak response, the Ministry of Health and Welfare of the Republic of Korea hosted several international joint missions that provided valuable information and recommendations for MERS control and prevention of future outbreaks. This report briefly summarizes the missions' outcomes and discusses their positive impacts.